Kiai-preneurs: A Case Study of Entrepreneurial Leadership Models in the Economic Transformation of Pesantren - Istianatul imamah; Siti Aimah (TA`DIBUNA, 2026)
This study aims to identify and analyze the Kiai-preneur leadership model in the economic transformation of pesantren. The research was conducted at Darussalam Pesantren, Blokagung, Banyuwangi, which has successfully developed various entrepreneurial-based business units. This study applied a qualitative approach with a case study design. Informants were purposively selected, consisting of the pesantren leader (Kiai), foundation board, business unit managers, teachers involved in entrepreneurship curriculum, as well as students and alumni representatives. Data were collected through in-depth interviews, participant observation, documentation, and audio-visual analysis. Data analysis employed Miles and Huberman’s interactive model with source, method, and observer triangulation to ensure credibility. The findings reveal that the leadership of the Kiai in Darussalam has evolved into a hybrid entrepreneurial-religious leadership, combining religious authority with modern entrepreneurial management. Key findings include: (1) integration of Islamic values in business management, (2) pesantren curriculum functioning as an entrepreneurship incubator for students and alumni, and (3) adoption of digitalization in pesantren businesses. The contribution of this research is to develop a hybrid entrepreneurial-religious leadership model (Kiai-preneurs), analyzing the specific practices of Koppontren Ausath, BLK Darussalam, and DASSCO as concrete evidence of the transformation of the pesantren economy through religious authority and modern entrepreneurial management